Pharmacovigilance of Neuroleptics and Benzodiazepines in the Psychiatric Teaching Hospital of Benin Republic - ALLABI, AUREL CONSTANT EUSTACHE; KLIKPO, TCHEDIE ELVIRE; Lonmandon, SC (My University, 2017)
Background: Data on adverse drug reactions (ADRs) related to neuroleptics and benzodiazepines in sub- Saharan Africa psychiatry setting are few indicating the need for psychotropic drugs safety surveillance in clinical care. Objective: To determine profile of the drugs prescribed, incidence, type and risk factors associated with adverse drug reactions (ADRs) among patients on neuroleptics and benzodiazepines. Methods: Patients initiated on neuroleptics and/or benzodiazepines between March 2014 and September 2014 were evaluated in a prospective cohort analysis. Prospective study of active pharmacovigilance during six months was performed. Each patient was followed for two months. The French method was used to determine the causality assessment. Results: 86 inpatients or outpatients were enrolled. 65.12% experienced a side event (SE). Among them, 22.09% had insomnia, 17.44%, drowsiness; 5.81%, dyskinesia; 4.65%, an appetite increase and 4.65%, headaches. The percentages of patients with 1, 2, 3, 4 and 5 side events were 39.28%, 41.07%, 8.92%, 7.14% and 3.57% of the 65.12% respectively. The average number of side events per patient was similar in hospitalized patients and in those treated ambulatory (1.97 vs. 1.92). The causality assessment of the side events to the drugs prescribed to each patient is predominantly doubtful (52.29%). It is likely in 44.95%, very likely in only 1.83% of the cases and plausible in 0.92% of the patients. All SEs occurred during the first month, most during the first week. The management of adverse drugs reactions led to drug doses reduction only in 23% of the cases while responsible drugs were stopped in 5.77% of the cases. Conclusion: The relatively high frequency of typical antipsychotics of use and low daily dose of benzodiazepine among our patients merit further investigation and systematic efficacy and safety monitoring. Typical antipsychotics should be made more available and monotherapies should be encouraged. The pharmacovigilance should be developed in the country by installing a National Center and by training health professionals.
Keywords: Adverse drugs reactions; Neuroleptics; Benzodiazepine; Benin; Pharmacovigilance